1997
DOI: 10.1016/s0001-2092(06)63080-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Rewarming Methods in a Postanesthesia Care Unit

Abstract: Postoperative hypothermia is problematic because patients in postanesthesia care units (PACUs) often feel very cold, and unrecognized or prolonged postoperative hypothermia can aggravate patients' underlying cardiovascular disorders. The researchers compared three methods of rewarming PACU patients who had undergone laparotomy procedures. Patients were assigned randomly to three groups. Each patient in group one received the standard PACU rewarming intervention (ie, two warmed thermal blankets and a hospital b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although not statistically significant, patients in the group covered with two warmed thermal blankets covered by a reflective blanket and then a hospital bedspread, reached normothermia on an average of eight minutes faster than the two other groups. 10 When comparing passive insulation with active rewarming (forced-air, warmed humidified oxygen, radiant warmers, etc), five RCTs (all Level II, Quality B) and one quasi-experimental study (Level III, Quality B) concluded that active rewarming is significantly more effective in the treatment of mild hypothermia than a standard application of cotton hospital blankets. This result clearly showed the superiority of active methods of warming over passive insulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not statistically significant, patients in the group covered with two warmed thermal blankets covered by a reflective blanket and then a hospital bedspread, reached normothermia on an average of eight minutes faster than the two other groups. 10 When comparing passive insulation with active rewarming (forced-air, warmed humidified oxygen, radiant warmers, etc), five RCTs (all Level II, Quality B) and one quasi-experimental study (Level III, Quality B) concluded that active rewarming is significantly more effective in the treatment of mild hypothermia than a standard application of cotton hospital blankets. This result clearly showed the superiority of active methods of warming over passive insulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although this physiologic response contributed to faster rewarming, shivering may be detrimental for recovering patients because of the increase in oxygen consumption and carbon dioxide production. 10 In three studies, authors used meperidine 12,15 or meperidine and small doses of nondepolarizing muscular blockers 13 for the treatment of postoperative shivering. Treatment of shivering with opioids may theoretically contribute to a prolonged length of stay among PACU patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative temperature management is becoming an area of increasing focus for perioperative personnel. The importance of initiating warming interventions in the preoperative phase is gaining recognition 19 . With the pressure to contain costs and maintain positive patient outcomes, clinically efficacious systems that provide cost‐effective alternatives to traditionally higher‐cost methodologies must be considered in today's ORs.…”
Section: Discussionmentioning
confidence: 99%
“…Os periódicos analisados eram dois médicos e um de enfermagem. Enfermagem, v. 07, n. 03, p. 266 -272, 2005 HERSHEY et al, (1997) desenvolveram um estudo onde procuraram testar a efetividade de 3 métodos de aquecimento para a recuperação da temperatura corporal dos pacientes na SRPA, sendo eles, como controle, dois cobertores aquecidos e a colcha da cama do hospital, grupo experimental 1, o método padrão do hospital mais o cobertor de alumínio reflexivo e grupo experimental 2, o método de aquecimento padrão mais o cobertor de alumino reflexivo mais reflective head covering (touca reflexiva? ), seus resultados demonstraram não haverem diferenças estatisticamente significantes entre os grupos.…”
Section: Caracterização Da Amostraunclassified